TRANSFORMASI BUDAYA MASYARAKAT DESA SERANGAN DI DENPASAR SELATAN DALAM PELESTARIAN SATWA PENYU - Sudiana, I Gusti Ngurah (Bumi Lestari; Vol 10 No 2 (2010), 2010)
The communities of Serangan have a habit to use turtle for trading, consumption, customs and religion. After the execution of Act of rare animal, the community became anxious, because it was prohibited using turtles for the above purposes. The community claimed the government so that it provided exemption using the turtles, but the government still wanted to preserve them. The two diversity of interests caused pro and contra of using the turtles so it aroused discourse internationally, nationally and regionally that gave an impact to the image of Bali society specifically the two villages was said as a society of turtles butcher by international world. The result of this research showed that before the execution of Act No: 7 and 8 in 1999 on the preservation of rare animal the use of turtle is a part of people of Serangan life for trading, consumption, custom and religious ritual. However since 2005 the use of turtle was changing from extractive to non extractive. Further there was also a changing in giving the meaning of turtle that is from exploitation to be the preserver through the release of tukik to the sea to maintain the balance of nature/sarwa bhuta hita. Since 2005 the use of turtle as religious ritual has been changing. Before 2005 the people used the big-size and large amount of turtles for ceremony. But since 2005 they are willing to use the small-size of turtles (boko), even if they did not get any single turtles, they replace it by using a duck. The changing of Serangan people perception regarding turtle that is from turtle consuming to turtle preserving can be found in awig-awig (adat law). Of adat village the turtle preservation was established, releasing tukik to the sea both as tourist attraction and as the form of turtle preservation that is taken from the conservation.
Keywords: culture; turtle; preservation; social cultural transformation